RNAi: antiviral therapy against dengue virus - Idrees, Sobia; Ashfaq, Usman A (Asian Pacific journal of tropical biomedicine, 2013)
Dengue virus infection has become a global threat affecting around 100 countries in the world. Currently, there is no licensed antiviral agent available against dengue. Thus, there is a strong need to develop therapeutic strategies that can tackle this life threatening disease. RNA interference is an important and effective gene silencing process which degrades targeted RNA by a sequence specific process. Several studies have been conducted during the last decade to evaluate the efficiency of siRNA in inhibiting dengue virus replication. This review summarizes siRNAs as a therapeutic approach against dengue virus serotypes and concludes that siRNAs against virus and host genes can be next generation treatment of dengue virus infection.